ANALYSIS OF THE EXPONENTS OF TRAIN DISPATCHERS - Mozolevych, H. Ya. (Science and Transport Progress, 2007)
There has been executed the research of the significants of the train dispatchers’ work. There has also been defined the characteristics of the random value distribution of the above significants.